Biosynthesis of Gold Nanoparticles by Aspergillus Niger And Their Role Against Pathogenic Bacteria - Alzamily, Ihsan Ali; Al-Shibly, Majid Kadhim; Hussein Ali, Zaman Abdul (Clinical Medicine And Health Research Journal, 2023)
The study included the use of Aspergillus niger filtrate for the biosynthesis of gold nanoparticles (GNPs) using a reducing medium designed for this purpose. The synthesis of Nanoparticles was verified by means of detections by spectrophotometry, X-ray diffraction, FTIR, and scanning electron microscopy. Nanoparticles were used to inhibit pathogenic bacteria obtained from urinary infections patients, and they included Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus by poisoning the nutrient medium and drilling method. It was also verified that there are no toxins accompanying the biosynthesis of these nanoparticles by the ammonia method. The detections of characterization of GNPs confirmed that the particles were synthesized in spherical, oval, and crystalline shapes with sizes ranging from a few nanometers to 500 nanometers, and they gave a light absorption band at the wavelength of 520 nanometers. Concerning the effect of GNPs on pathogenic bacteria, the method of poisoning the media confirmed that the 15% concentration was significantly effective against the three bacterial species, as it gave the lowest diameter of colony growth (1.1, 1.6, 2.3) cm for Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus respectively. As for the drilling method, it also showed a high significant ability of 15% concentration to inhibit the tested bacteria by measuring the inhibition zone, which gave an area of ​​(5.1, 5.4,6) cm for Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus respectively, with regard to the toxicity test, the study showed that the isolate used in the synthesis does not produce toxins, which confirms its suitability and dependence in the biosynthesis of nanoparticles.